Advantages and challenges of the geodetic electronic cabinet in Lviv territorial community - Malanchuk, M.; Rybitskyi, R. (Land Management, Cadastre and Land Monitoring, 2024)
Abstract: This article analyzes the main advantages and drawbacks of the geodetic electronic cabinet, a new online service for submitting topographic and geodetic works in the Lviv Territorial Community (TC). It demonstrates its role in both digital transformation and the establishment of a local geoinformation database. Through research, its high efficiency, informativeness, and convenience at every stage of work, from issuing initial data to signing, have been revealed. The article examines the process of submitting topographic-geodetic works before the cabinet's creation to better understand its advantages. Additionally, it identifies problems with accessing the geodetic electronic cabinet, citing examples of technical glitches on the website due to its relative novelty, which occasionally halted the entire surveying process. The article also illustrates how the creation of the Lviv TC complicated the process of submitting and signing topographic-geodetic works through the electronic cabinet. It highlights the complete lack of a digital topographic base suitable for processing and submitting surveys in all settlements of the community except Lviv city. The study identifies and outlines solutions to two critical problems significantly slowing down the work submission process in the Lviv territorial community: issues with red lines and engineering networks. It predicts that in the future, more territorial communities will utilize the geodetic electronic cabinet to submit topographic-geodetic works to local government bodies.Keywords: geodetic electronic cabinet, digital transformation, topographic-geodetic works, Lviv TC, engineering networks, red lines, topographic base, geoservice sector, and engineering networks.
Keywords: geodetic electronic cabinet; digital transformation; topographic-geodetic works; Lviv TC; engineering networks; red lines; topographic base; geoservice sector and engineering networks